Single Cell Transcriptomics: Methods and Applications - Kanter, Itamar; Kalisky, Tomer (Frontiers in Oncology, 2015)
Traditionally, gene expression measurements were performed on "bulk" samples containing populations of thousands of cells. Recent advances in genomic technology have made it possible to measure gene expression in hundreds of individual cells at a time. As a result, cellular properties that were previously masked in "bulk" measurements can now be observed directly. In this review we will survey emerging technologies for single cell transcriptomics, and describe how they are used to study complex disease such as cancer, as well as other biological phenomena such as tissue regeneration, embryonic development, and immune response.